(untitled) (Global Journal of Science Frontier Research, 2017)
This research was conducted to know the biological composition and biodiversity of Rotifera in Al-Shamyiah River . For this purpose, four stations were selected on the river. The samples were collected monthly for the period from March 2012 until February 2013. The relative abundance index results showed that species Keratella valga and K. cochlearis and Monostyla bulla are among the most abundant taxonomic units relative to river water . The constancy index showed the presence of 12 constant taxonomic units in this river. However the other taxonomy units varied from "accessory" and "accidental" taxonomic units in study stations. During this study of 88 taxonomic units of rotifera were identified. Values of species richness index of rotifera group varied from 0-13.05. The total Shanon-Weiner index varied from 0-3.58 bit/Ind.. The species uniformity index of rotifera group varied from 0-0.94, and these high values indicate that there is no ecological stress on rotifera in Al-Shamyiah River environment.